2022
DOI: 10.1177/11206721221084764
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety profile of cataract procedures performed with a sensor-embedded handpiece and a new hybrid phaco tip

Abstract: Objective To evaluate the efficacy and safety of the new Intrepid Hybrid tip and Active Sentry handpiece in comparison to the Intrepid Balanced tip and Centurion Ozil handpiece. Methods One hundred sixty-eight eyes were included in the study and randomized into Group 1 (Active Sentry handpiece + Intrepid Hybrid tip, n = 86) and Group 2 (Centurion Ozil handpiece + Intrepid Balanced tip, n = 82). Data were collected from the phaco device, including total U/S time, cumulative dissipated energy (CDE), the total nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…[13] Sabur H. et al reported that ASM actuations were more engaged in the eyes with pseudoexfoliation and small pupils. [25] In our results, Anti-surge (times), phacoemulsi cation time (seconds), CDE, and BSS use (ml) of the handpiece group were signi cantly increased in patients with zonule weakness and poor mydriasis compared with patients without, respectively (p < 0.05) (Table 3). And, anti-surge (times), phacoemulsi cation time (seconds), CDE, and BSS use (ml) were signi cantly increased according to increasing nucleosclerosis grades in the handpiece group, respectively (p < 0.05) (Table 2).…”
Section: Discussionmentioning
confidence: 49%
“…[13] Sabur H. et al reported that ASM actuations were more engaged in the eyes with pseudoexfoliation and small pupils. [25] In our results, Anti-surge (times), phacoemulsi cation time (seconds), CDE, and BSS use (ml) of the handpiece group were signi cantly increased in patients with zonule weakness and poor mydriasis compared with patients without, respectively (p < 0.05) (Table 3). And, anti-surge (times), phacoemulsi cation time (seconds), CDE, and BSS use (ml) were signi cantly increased according to increasing nucleosclerosis grades in the handpiece group, respectively (p < 0.05) (Table 2).…”
Section: Discussionmentioning
confidence: 49%
“…Also, besides removing opacified lenses one can significantly reduce the risk of postoperative corneal astigmatism with smaller incision sizes and sophisticated intraocular lenses, resulting in good postoperative visual acuity through refractive correction [ 24 ]. More efficient energy transmission to the phaco tip was reported for Group-M than Kelman tips [ 25 ]; and safer crushing and aspiration of lens cortex and nucleus due to the polymer overmold of a Group-P tip avoided damage to the iris and lens capsule [ 24 ]. There have been few reports of the polymer overmold tip; one compared efficacy and safety among the Active Sentry handpiece with Group-P and the Centurion OZil handpiece with Group-M in clinical surgical data, and reported the former showed significantly lower cumulative dissipated energy and torsional amplitude with no cataract surgery complications observed [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that recent cataract surgery requires less energy to emulsify opacified lenses as previously, since the number of cases presenting with high grades and hard nuclei has decreased [15][16][17][18][19][20][21][22][23]. Also, besides removing opacified lenses one can significantly reduce the risk of postoperative corneal astigmatism with smaller incision sizes and sophisticated intraocular lenses, resulting in good postoperative visual acuity through refractive correction [24]. More efficient energy transmission to the phaco tip was reported for Group-M than Kelman tips [25]; and safer crushing and aspiration of lens cortex and nucleus due to the polymer overmold of a Group-P tip avoided damage to the iris and lens capsule [24].…”
Section: Plos Onementioning
confidence: 99%
“…This study compared U/S time between the iChopper and control groups in each institution because U/S time was recorded differently by each phacoemulsification machine (effective phacoemulsification time [EPT], total U/S time, and EFX [U/S % and time used during phacoemulsification]). 20,21 This study conducted a chi-square test to compare laterality. A repeated-measures analysis of variance (ANOVA) was conducted to compare UDVA, CDVA, corneal ECD, hexagonality, CoV, central macular thickness, CCC size, and ACO and PCO scores during the follow-up periods between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%